Headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS) and odor activity value (OAV) to reveal the flavor characteristics of ripened Pu-erh tea by co-fermentation - Zheng, Yaru; Zhang, Chunhua; Ren, Dabing; Bai, Ruoxue; Li, Wenting; Wang, Jintao; Shan, Zhiguo; Dong, Wenjiang; Yi, Lunzhao (Frontiers in Nutrition, 2023)
Introduction Pu-erh tea is a geographical indication product of China. The characteristic flavor compounds produced during the fermentation of ripened Pu-erh tea have an important impact on its quality. Methods Headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS) and odor activity value (OAV) is used for flavor analysis. Results A total of 135 volatile compounds were annotated, of which the highest content was alcohols (54.26%), followed by esters (16.73%), and methoxybenzenes (12.69%). Alcohols in ripened Pu-erh tea mainly contribute flower and fruit sweet flavors, while methoxybenzenes mainly contribute musty and stale flavors. The ripened Pu-erh tea fermented by Saccharomyces: Rhizopus: Aspergillus niger mixed in the ratio of 1:1:1 presented the remarkable flavor characteristics of flower and fruit sweet flavor, and having better coordination with musty and stale flavor. Discussion This study demonstrated the content changes of ripened Pu-erh tea’s flavor compounds in the fermentation process, and revealed the optimal fermentation time. This will be helpful to further understand the formation mechanism of the characteristic flavor of ripened Pu-erh tea and guide the optimization of the fermentation process of ripened Pu-erh tea.